UPAYA GURU DALAM MENINGKATKAN HAPALAN KOSA KATA BAHASA ARAB MELALUI METODE MENYANYI PADA ANAK USIA DINI - Zr, Jamilah; Suryani Siregar, Lanny; Hesty Sagala, Pebrina; Meiniza Nasution, Yelvira; Zahra Lubis, Hilda (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
This journal aims to determine teachers' efforts to improve memorization of Arabic vocabulary through singing methods in early childhood. This research uses qualitative research with a literature review method, which means analyzing previous research journals. Early childhood education is essentially education that is organized to facilitate the child's overall growth and development and emphasizes the development of all aspects of the child's personality. Therefore, the teacher's efforts are to provide opportunities for children to develop their personality and potential to the maximum. The use of the singing method is the development of an information processing model so that children can more easily understand and digest Arabic vocabulary using the media that children hear. The singing method is a tool to stimulate children's thinking patterns or brain stimulation so that children can first hear what they are learning.